2020
DOI: 10.1371/journal.pone.0230680
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the edible mushroom Lentinula edodes in response to blue light

Abstract: Lentinula edodes is one of the most popular edible mushrooms worldwide and contains important medicinal components such as lentinan, ergosterol, and eritadenine. Mushroom metabolism is regulated by the mycelia and fruit body using light; however, in mushrooms, the underlying molecular mechanisms controlling this process as well as light-induced gene expression remain unclear. Therefore, in this study, we compared morphological changes and gene expression in the fruit bodies of L. edodes cultivated under blue l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 50 publications
1
30
0
2
Order By: Relevance
“…Ubiquinone and other terpenoid−quinone biosynth... domain-containing protein (B50aA0120), an important oxidoreductase with a role in electron transfer, 29 was significantly upregulated in group B, while ZIP zinc/iron transport family (B50aA1280) and potassium/sodium efflux P-type ATPase (B50aA4199) were all downregulated with higher expression in group B.…”
Section: Pyrimidine Metabolismmentioning
confidence: 99%
“…Ubiquinone and other terpenoid−quinone biosynth... domain-containing protein (B50aA0120), an important oxidoreductase with a role in electron transfer, 29 was significantly upregulated in group B, while ZIP zinc/iron transport family (B50aA1280) and potassium/sodium efflux P-type ATPase (B50aA4199) were all downregulated with higher expression in group B.…”
Section: Pyrimidine Metabolismmentioning
confidence: 99%
“…Work by many of the same authors has also developed quantitative trait loci (QTL) associated with important agronomic traits 3 , 6 , 21 , 26 . Furthermore, RNA-Seq experiments have been conducted to understand how Shiitake responds to different environments and treatments 27 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Several gene ontology (GO) classifications related to brown film formation were revealed by two-dimensional electrophoresis combined with the matrix-assisted laser desorption/ionization tandem time-of-flight mass spectrometry approach and included small molecule metabolic processes, response to oxidative stress, and organic substance catabolic processes ( Tang et al, 2016 ). Kim et al (2020) compared the morphological changes and gene expression of Lentinus edodes under blue light and continuous dark conditions. Their results indicated that the differential genes were involved in the morphological development of primordia and embryonic muscle, cell adhesion and the structure of cellulose and non-cellulose cell walls that affect the development of fruiting bodies, as well as photoreceptors of blue light signals for fruiting body development and pigment formation ( Kim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… Kim et al (2020) compared the morphological changes and gene expression of Lentinus edodes under blue light and continuous dark conditions. Their results indicated that the differential genes were involved in the morphological development of primordia and embryonic muscle, cell adhesion and the structure of cellulose and non-cellulose cell walls that affect the development of fruiting bodies, as well as photoreceptors of blue light signals for fruiting body development and pigment formation ( Kim et al, 2020 ). Blue light is an important environmental factor in inducing primordial differentiation and the fruiting body development of mushrooms, such as Hypsizygus marmoreus, Pleurotus ostreatus , and Coprinus cinereus ( Kues et al, 1998 ; Terashima et al, 2005 ; Xie et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation